A method for the measurement of leakage current due to surface discharge at the oil-pressboard interface - Zainuddin, Hidayat; Mitchinson, P.M.; Lewin, P.L. (2011)
Surface tracking is the conducting path formed on the surface of an insulation material as a result of surface currents. Tracking has commonly been associated with solid insulation in air such as overhead line insulators but is now recognized to occur at the oil-pressboard insulation interface inside large transformers. The surface current is effectively the drift of charge under the action of an electric field which may be either the general electric field or a locally enhanced field developed around a space charge. A needle-bar configuration has been developed to promote surface tracking under controlled conditions at the oil-pressboard interface without surface flash-over or breakdown. This method is used to study the leakage current associated with surface discharge applied from a high voltage source on the oil-pressboard interface. This paper outlines the experimental set-up and presents results which compare the measured current against the corresponding partial discharges. Subsequently a mechanism describing the process by which leakage current is formed is proposed.